Network Security Using Honeypot and Attack Detection with Android Application - Herman Yuliandoko; Agus Priyo Utomo; Farizqi Panduardi (Indonesian Journal of Engineering Research, 2021)
Network security is now increasingly needed in the era of the industrial revolution 4.0. As technology grows, cybercrimes are becoming more and more common, including attacks on a resource. At this time, honeypots are also widely used by large industries for network security, besides that honeypots are also useful for them in developing intrusion and preventing systems. Honeypots are usually used in a virtual environment, they will stimulate a fake system to capture data packets on the network and be analysed offline later for all threats and attacks. This propose of this paper is to detect and prevent building attacks from computer network attackers using an android application. This application can monitor an attack on the server by installing a honeypot tool into the server as an attack detector, then the honeypot log is used as a Rest API using Django framework with MongoDB database. this application can find out if there is an attack on the server, and can block the attacker's IP address.